Determinants of islamic credit card usage among Muslims in Kuala Lumpur / Azyan Syamimi Shalahuddin - Shalahuddin, Azyan Syamimi (2012)
The development of everyday financial instruments is an important dimension of modern life, and credit cards are considered to be the main instruments and facilitators of spending in modern economies. Together with the Internet, which facilitates the spending process, credit cards have become essential instruments of spending. In response to this, and due to the expansion of Islamic banking and finance, the Islamic equivalent of credit cards (Islamic credit cards or ICCs) have been engineered with their own sophisticated financing methods alongside conventional credit cards (CCCs). Malaysia is one of the pioneering countries in Islamic finance and has developed a number of ICC products. The objective of this study was to examine the determinants of the Islamic credit card usage among Muslims in Kuala Lumpur. There are three factors being studied, which were: income, religiosity and attitudes. As Kuala Lumpur City Centre (KLCC) had been chosen as the unit of analysis for this study. In conducting the research, this study assembled primary data from Malaysia through a questionnaire survey with 100 participants. In addition, interviews with cardholders were conducted to verify the results that were established through a quantitative data analysis of the questionnaire. The data collected being test on five methods, which frequencies, descriptive, reliabilities, correlation and regression analysis. Besides, regression analysis was used to test the hypotheses in this study. The findings of this paper suggest that the income, religiosity and attitudes are significant factors in explaining Islamic credit card usage among Muslims in Kuala Lumpur. This study is useful for various parties, including customers, to examine how credit cards can create financial difficulty. It will also aid financial issuers in understanding the attitudes and perceptions of cardholders, hence, allowing a better strategy in structuring their credit cards